Beneficial Effects of Propionyl L-Carnitine Therapy in Diabetic Cardiomyopathy - Kaur, Khushman; Kirshenbaum, Lorrie; Tappia, Paramjit S; Dhalla, Naranjan S (Scripta Medica, 2025)
In this review, the beneficial effects of metabolic therapy with propionyl L-carnitine (PPLC) on cardiovascular complications during the development of diabetic cardiomyopathy was evaluated. Since metabolic abnormalities due to mitochondrial dysfunction are invariably associated with deficiency of carnitine, accumulation of toxic long-chain derivatives of fatty acids and development of oxidative stress in the heart, it appears that the effects of PPLC therapy are related to the attenuation of these derangements. Particularly, the beneficial effects of PPLC therapy in improving cardiac function in chronic diabetes were associated with attenuation of increase in sarcolemmal Ca2+-binding and Ca2+-ecto ATPase activities. Furthermore, depressed sarcolemmal Na+-K+ ATPase and Na+-dependent Ca2+-uptake as well as sarcoplasmic reticulum Ca2+-pump activities in diabetic hearts were attenuated by PPLC therapy. These actions of PPLC therapy were accompanied by improvement in mitochondrial oxidative phosphorylation and attenuation of changes in the high energy phosphate stores in the diabetic heart. Since incubation of sarcolemma with PPLC was found to reduce the inhibitory actions of palmitoyl L-carnitine on Na+-K+ ATPases and Na+-dependent Ca2+-uptake, it is suggested that PPLC therapy may attenuate cardiac abnormalities by antagonising the deleterious actions of accumulated long- chain lipids in diabetic cardiomyopathy.
Keywords: Diabetic cardiomyopathies; Propionyl L-carnitine; Palmitoyl L-carnitine; Oxidative stress; Sarcolemma; Sarcoplasmic reticulum; Mitochondria